Minimally Invasive Cancer Management - Greene, Frederick L.; Heniford, B. Todd.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
As minimal access approaches to cancer diagnosis, staging, and therapy become more widely used, it is vital for general surgeons, along with laparoscopists, surgical oncologists and medical oncologists, to stay up to date. The editors, a team consisting of a renowned surgical oncologist and a laparoscopic specialist, aim to provide a resource for the practicing general surgeon using basic minimally invasive techniques. The book discusses diagnosis including biopsy with microinstrumentation, staging, and palliative and curative resection. Specific tumor sites are addressed, including esophagus, stomach, spleen, small bowel, pancreato-biliary, hepatic resection, and colo-rectal resection. Minimally invasive approaches to the thoracic and retroperitoneal areas are included. The book provides a thorough overview of basic cancer biology, instrumentation, and ultrasound. Additionally, Greene and Heniford explore controversial issues such as port-site recurrence and the effect of pneumoperitoneum on the spread of cancer cells in the abdomen. Many photographs and line drawings, including 16 in full color, illustrate the principles discussed in the text. A must-have for every practicing general surgeon, laparoscopic fellow, and general surgery resident.
Introductory Issues -- Indications and General Oncologic Principles -- Cancer Biology Relating to Minimal Access Management -- Pneumoperitoneum: Metabolic and Mechanical Effects -- Energy Sources in Laparoscopy -- Biopsy and Staging: Technical Issues -- Ultrasound Techniques in Minimally Invasive Oncologic Surgery -- Management of Foregut Cancer -- Endoscopic Ablation of Barrett$1 (Bs Esophagus and Early Esophageal Cancer -- Management of Esophageal Cancer -- Laparoscopic Resection of Gastrointestinal Stromal Tumors -- Laparoscopic Approaches to Gastric Cancer -- Management of Hepatopancreaticobiliary Cancer -- Minimal Access Management of Pancreatic Cancer -- Laparoscopic Approaches to Pancreatic Endocrine Tumors -- Laparoscopic Approaches to Hepatobiliary Cancer -- Laparoscopic Approaches to Colonic Malignancy -- Laparoscopic Resection of Rectal Cancer -- Transanal Endoscopic Microsurgery (TEM) -- Laparoscopic Ablation of Liver Tumors -- Laparoscopic Management of Other Solid Organs -- Laparoscopic Splenectomy for Malignant Diseases -- Laparoscopic Management of Renal Cell Carcinoma -- Laparoscopic Adrenalectomy for Metastatic Cancer -- Minimally Invasive Approaches to Lung Cancer -- Laparoscopy in Gynecologic Malignancies -- Special Issues in Cancer Management -- Minimally Invasive Surgery in Pediatric Oncology -- Endoscopic Diagnosis and Treatment of Breast Diseases -- The Applications of Sentinel Lymph Node to Cancer -- Future Prospects.s
Keywords: Medicine; Oncology; Surgery; Medicine & Public Health; General Surgery; Oncology